2009
DOI: 10.1038/sj.bjc.6604931
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of differential gene expression in colorectal cancer and stroma using fluorescence-activated cell sorting purification

Abstract: Tumour stroma gene expression in biopsy specimens may obscure the expression of tumour parenchyma, hampering the predictive power of microarrays. We aimed to assess the utility of fluorescence-activated cell sorting (FACS) for generating cell populations for gene expression analysis and to compare the gene expression of FACS-purified tumour parenchyma to that of whole tumour biopsies. Single cell suspensions were generated from colorectal tumour biopsies and tumour parenchyma was separated using FACS. Fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 52 publications
4
15
0
Order By: Relevance
“…This fact can be due to a higher level of stromal components in the peripheral part of the tumor than in its central part. The change of the expression profile corresponds to data obtained from colorectal cancer research that reported the predominance of proteins forming components of extracellular matrix: collagens, tissue inhibitors of matrix metalloproteins (COL6A3, COL1A2, POSTN, TIMP2 and others) at the peripheral part of the tumor [10].…”
Section: Discussionsupporting
confidence: 77%
“…This fact can be due to a higher level of stromal components in the peripheral part of the tumor than in its central part. The change of the expression profile corresponds to data obtained from colorectal cancer research that reported the predominance of proteins forming components of extracellular matrix: collagens, tissue inhibitors of matrix metalloproteins (COL6A3, COL1A2, POSTN, TIMP2 and others) at the peripheral part of the tumor [10].…”
Section: Discussionsupporting
confidence: 77%
“…COL6 upregulation has been reported in various aspects of tumor progression. Malignant cancer cells can also express COL6; this has been reported for the mammary gland (18), the colon (35,36), pancreatic ductal adenocarcinomas (37), and hepatocarcinomas (38). Thus, the source of ETP in the tumor microenvironment may be heterogeneous, with signals cooperatively influencing cancer cell behavior through paracrine and autocrine pathways.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, a spectrum of studies has reported the suppression of MYC by miRNAs, including let-7a (40), miR-23a/b (41) and miR-145 (42), in various cancer types. Furthermore, the overexpression of stromal genes, such as collagen type I α2 chain (COL1A2), was also detected in CRC (43). …”
Section: Discussionmentioning
confidence: 99%